TOPONIMI NAMA PANTAI DI BELITUNG - Filia, Filia (Paradigma: Jurnal Kajian Budaya, 2024)
This research examines the toponymy of beaches in Belitung using the socio-onomastic approach. The names of beaches in Belitung Regency were studied using written and oral data. The written data was obtained from three maps, i.e., the map from the Geospatial Information Agency, the geological map of Belitung and the digital Google Maps. The oral data was obtained through interviews with resource persons and informants in Belitung. Based on map searches and interviews, seven beach names and the origin of their names have been obtained, as follows (i) Tanjung Tinggi Beach, (ii) Tanjung Pendam Beach, (iii), Penyabong Beach, (iv) Tanjung Kelayang Beach, (v) Tanjung Binga Beach, (vi) Bukit Berahu Beach, and (vii) Batu Bedil Beach. In addition to these beaches, there may be other beach names worth examining. Beach names in Belitung Regency have four naming patterns: (i) beach toponyms with elements of topography, (ii) beach toponyms with elements of topography and fauna, (iii) beach toponyms with elements of topography and flora, and (iv) beach toponyms with elements of sound. Sometimes, a beach has more than one name. From socio-onomastics perspective, it is a natural phenomena, because names of place have various characteristics and influence people’s preferences in using names.